تأثير استخدام كتيّب اللّغة العربيّة لترقّية قدرة مهارة الكلام لدى الطّلاّب في معهد التّربية الإسلاميّة تاروسان كامانج - Fatma Nurul Guci; Wira Wahyuni (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2026)
This study, entitled “The Effect of Using Arabic Pocket Books on Improving Students’ Speaking Skills at MTI Tarusan Kamang Islamic Boarding School”, was conducted to address the low speaking ability and limited vocabulary of students as well as the lack of engaging learning media. The purpose of this research is to examine whether the use of Arabic pocket books significantly improves students’ speaking skills. This research employed a quantitative method with a pre-experimental approach using a One Group Pretest-Posttest Design. The sample consisted of 26 students from a special class selected through purposive sampling. Data were collected through oral pretests and posttests to measure speaking performance before and after the treatment. Analysis was carried out using the Paired Sample t-Test with the assistance of SPSS. The findings revealed a significant improvement in students’ speaking skills after the use of Arabic pocket books. The t-test results showed that the t-count exceeded the t-table at the 5% significance level (23.57692 > 2.0595), leading to the rejection of Ho and acceptance of Ha. Thus, the use of Arabic pocket books is proven to be an effective and practical learning medium to enhance students’ speaking skill Keywords: Pocket Book, Learning Media, Speaking Skill